2012
DOI: 10.1111/birt.12002
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Variation, Intervention, and Outcomes: Doing More but Accomplishing Less

Abstract: Obstetric interventions, particularly induction of labor and cesarean section, are done more and more commonly, although there is a wide variation between hospitals and practitioners in specific rates. This degree of variation implies imprecision and uncertainty about diagnoses and indicated management. Although the net result of this variation has been a "more is better" approach leading to increasing use of obstetric interventions, little evidence of commensurate improvements in outcome is available. A combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 24 publications
5
36
0
Order By: Relevance
“…The midwifery philosophy of care emphasizes the inherent normalcy of birth, and midwives may bring this attitude with them to the labor and delivery unit in ways that change patterns of care provision . Hospital administration that is supportive of midwifery may shape the broader environment as well, or be indicative of a commitment to reducing unwarranted procedure use . Hospitals where midwives attend a larger proportion of the births may also structure their care for women differently; for example, one hospital combined a midwifery service with a laborist model of care and found that this resulted in lower rates of primary cesarean birth and higher rates of vaginal birth after cesarean (VBAC) .…”
Section: Discussionmentioning
confidence: 99%
“…The midwifery philosophy of care emphasizes the inherent normalcy of birth, and midwives may bring this attitude with them to the labor and delivery unit in ways that change patterns of care provision . Hospital administration that is supportive of midwifery may shape the broader environment as well, or be indicative of a commitment to reducing unwarranted procedure use . Hospitals where midwives attend a larger proportion of the births may also structure their care for women differently; for example, one hospital combined a midwifery service with a laborist model of care and found that this resulted in lower rates of primary cesarean birth and higher rates of vaginal birth after cesarean (VBAC) .…”
Section: Discussionmentioning
confidence: 99%
“…43 It is problematic to specify the correct or target intervention rate such as a hospital IOL rate, particularly when the appropriate rate is likely to differ according to the ‘induction group’. Instead, the focus should be on achieving the best outcomes for mothers and babies with minimum intervention,1 reflecting not only improved clinical decision-making, but also efficient resource management. Hospitals that have lower rates of IOL, yet have the same outcomes for mothers and babies compared to hospitals with higher rates of IOL, provide opportunities to suggest changes in clinical practice for other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, for many medical interventions including in obstetrics,1 much of the clinical practice variation is unexplained (ie, not due to patient profiles, preferences or medical science) 2. Unexplained clinical practice variation questions the appropriate usage of scarce resources,3 whether medical interventions are too few or too many, and whether healthcare provision is efficient or effective 4…”
Section: Introductionmentioning
confidence: 99%
“…Rates of older women giving birth, inductions of labour, and macrosomia have also increased, [40][41][42] and are all risk factors to be considered when a trial of vaginal delivery is discussed. In the clinical situation, with a woman attempting vaginal birth after a prior caesarean section, knowledge of risk factors that can be influenced during labour, such as method of induction, management of protracted labour, use of oxytocin, and epidural analgesia, is of importance, and should be taken into consideration when assessing the health and safety of woman and child.…”
Section: Discussionmentioning
confidence: 99%